AN ANALYSIS OF COHESIVE DEVICES IN HIRATA’S “THE RAINBOW TROOPS” NOVEL - Nabila Khoirunnisa; Jufrizal Jufrizal; Leni Marlina (Universitas Negeri Padang, 2018)
Novel is a kind of literacy work that contains of sentences. Every sentences has grammatical and lexical devices in sentences or text that is called cohesive devices. This study aims at to know the types of cohesive devices in novel written by an Indonesian popular writer, Andrea Hirata. The title of the novelis Laskar Pelangi, that novel has been translated into English entitled “The Rainbow Troops”. This Study analyze English version of this novel. The method to analyze is descriptive qualitativee. The data of this study are all sentences that contain of cohesive devices in chapter 30 of this novel. The result of this study show that, all types of grammatical and lexical devices exist in chapter 30. Where, grammatical devices is the mostly used in this chapter. Reference devices are the mostly used than the two grammatical, substitution and conjunction. Personal reference is a type of reference devices. It can be proved base on discussion of this research, give the fact that reference device is a criteria of child literature, in this case is Andrea Hirata’s The Rainbow Troops novel talk about children and their childhood. From the previous study also concluded that, children writing also have reference devices as the most frequently used in their writing about literature.